(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Recently many research projects related to the design of earthquake resistant structures and various robust construction methods are expected to be earthquakes and the study explains two major methods of Force Based Design (FBD) and Direct Displacement Based Design(DDBD) in which the first is a Conventional method, while later one is an approach to design performance. Design and analysis were in bare-frame dimensions of four, eight and twelve stories based on the following IS 456, IS 1893 codes: 2000, ETABSA and two design approaches should be studied. As the earthquake design approaches, DDBD has been widely accepted by the above method, based on the FBD. In their process, the FBD uses the building displacement as the final test to determine the structural performance, while the DDBD uses as a defined performance target. If the final displacement to FBD larger is the value specified by the template, then the design process must be recalculated. In addition, under some common practices, DDBD is simpler than FBD.